Overlapping Authority on the Cancellation of Local Regulation (An Erroneous Logic of Local Autonomy) - Retno Mawarini Sukmariningsih (Hasanuddin Law Review, 2017)
This research is based on the phenomenon of weak supervision on local law products. As a result, the province of Central Java became the region with the largest cancellation of local regulation in Indonesia, which is as many 90-local regulations cancelled. The cancellation of local regulation implicates the obstacles in the implementation of development and district and municipal programs in Central Java - Indonesia. The purpose of this research was to analyze the authority of the region in order to avoid overlapping authority on the cancellation of local regulation by the Governor as the representative of the Central Government. The method of writing uses a normative approach with qualitative analysis to detect the level of synchronization and harmonization of the application of local regulations. The results indicate that the cancellation of local regulation by the Governor as the representative of the central government shows an erroneous logic of the implementation of local autonomy. Ideally, the cancellation of local regulation is performed “one gate”, i.e by the Supreme Court (judicial institution only) through the authority of judicial review